Functional analysis of the Fusarium graminearum phosphatome - Yun, Yingzi; Liu, Zunyong; Yin, Yanni; Jiang, Jinhua; Chen, Yun; Xu, Jin‐Rong; Ma, Zhonghua (The New phytologist, 2015)
Phosphatases are known to play important roles in the regulation of various cellular processes in eukaryotes. However, systematic characterization of the phosphatome has not been reported in phytopathogenic fungi. The wheat scab fungus Fusarium graminearum contains 82 putative phosphatases. The biological functions of each phosphatase were investigated in this study. Although 11 phosphatase genes appeared to be essential, deletion mutants of the other 71 phosphatase genes were obtained and characterized for changes in 15 phenotypes, including vegetative growth, nutrient response and virulence. Overall, the deletion of 63 phosphatase genes resulted in changes in at least one of the phenotypes assayed. Interestingly, the deletion of four genes (Fg06297, Fg03333, Fg03826 and Fg07932) did not dramatically affect hyphal growth, but led to strongly reduced virulence. Western blot analyses showed that three phosphatases (Fg10516, Fg03333 and Fg12867) functioned as negative regulators of the mitogen-activated protein kinase signaling pathways. In addition, we found, for the first time, that FgCdc14 is dispensable for growth, but plays an important role in ribosome biogenesis. Overall, in this first functional characterization of the fungal phosphatome, phosphatases important for various aspects of hyphal growth, development, plant infection and secondary metabolism were identified in the phytopathogenic fungus F. graminearum.